2013
DOI: 10.1080/15287394.2013.830584
|View full text |Cite
|
Sign up to set email alerts
|

Determination of TiO2, ZrO2, and Al2O3Nanoparticles on Genotoxic Responses in Human Peripheral Blood Lymphocytes and Cultured Embyronic Kidney Cells

Abstract: In this study a genotoxic evaluation of titanium dioxide (TiO2, 2.3 nm), zirconium oxide (ZrO2, 6 nm), aluminum oxide (Al2O3, 16.7 nm) nanoparticles (NP) and their ionic forms was conducted using human peripheral blood lymphocytes and cultured human embryonic kidney (HEK293) cells by means of a modified alkaline comet assay with/without the formamidopyrimidine-DNA glycosylase (Fpg) and endonuclease III (Endo III) enzymes. Modifications to the comet assay by using lesion-specific endonucleases, such as Endo III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Ghosh et al () reported an increase only at the lowest dose (25 μg ml −1 ) in PBMCs treated for 3 hours with TiO 2 (crystalline phase not reported) of 50 nm size. Conversely, Demir, Burgucu, Turna, Aksakal, and Kaya () observed an increase only at the highest dose tested (100 μg ml −1 ) after treatment of PBMCs for 3 hours with TiO 2 NPs of 2.3 nm size (crystalline phase not reported). Finally, Hackenberg et al () failed to observe any DNA damage increase in PBMCs after 24 hours of treatment with 20–200 μg ml −1 anatase NPs (<25 nm).…”
Section: Discussionmentioning
confidence: 94%
“…Ghosh et al () reported an increase only at the lowest dose (25 μg ml −1 ) in PBMCs treated for 3 hours with TiO 2 (crystalline phase not reported) of 50 nm size. Conversely, Demir, Burgucu, Turna, Aksakal, and Kaya () observed an increase only at the highest dose tested (100 μg ml −1 ) after treatment of PBMCs for 3 hours with TiO 2 NPs of 2.3 nm size (crystalline phase not reported). Finally, Hackenberg et al () failed to observe any DNA damage increase in PBMCs after 24 hours of treatment with 20–200 μg ml −1 anatase NPs (<25 nm).…”
Section: Discussionmentioning
confidence: 94%
“…Peripheral blood lymphocytes died after exposure to nanoparticles containing silicon and carbon nanotubes, an effect that was dependent on the concentration of the nanoparticles employed [51,52]. TiO 2 , ZrO 2 , and Al 2 O 3 nanoparticles did not damage these cells' DNA at concentrations of 1, 10, and 100 μg/mL [53]. Nanoparticle size seems to influence toxicity.…”
Section: Interaction Of Nanomaterials With Peripheral Mononuclear Cellsmentioning
confidence: 98%
“…Major concerns are coming up due to the release of nanosized Cd particles, especially cadmium oxide nanoparticles (CdO NPs) and cadmium sulfide nanoparticles (CdS NPs) from the industries involved in manufacturing quantum dots for biomedical usage (Bentolila et al 2005;Blum et al 2012;Yang et al 2012). Synthesized metal NPs are now being released into the environment in many ways and are emerging as potential environmental contaminants (Oberd€ orster, Oberd€ orster, and Oberd€ orster 2005; Thill et al 2006;Horst et al 2010;Demir et al 2013;Park 2013). Thus, investigation for understanding the toxicological impact of released NPs in the environment is warranted.…”
Section: Introductionmentioning
confidence: 98%